Postoperative changes in nonspecific low back pain after atlantoaxial stabilization surgery - Sezer, Can; Açıkalın, Rıdvan (The European Research Journal, 2023)
Objectives: Posterior atlantoaxial stabilization can be technically challenging. Postoperative C2 nerve dysfunction occurs as a complication of this procedure or when a lateral mass is exposed and sacrificed for screw placement. Patients with cervical pathology sometimes complain of low back pain simultaneously. In this study, we aimed to investigate the results of C1-C2 posterior stabilization and C2 nerve root sacrifice on postoperative lumbar complaints. Methods: Twenty-six patients who underwent multicentric posterior C1-C2 stabilization due to atlantoaxial dislocation were retrospectively included in the study. Those that were not sacrificed the C2 nerve root during stabilization were considered group 1 (n = 12), and those that were sacrificed the C2 nerve root were considered group 2 (n = 14). A visual Analogue Scale (VAS) was used for the neck, arm, low back, and leg pain. The EQ-5D Index was used as the overall quality of life scale. Results: Six months postoperatively, both groups showed significant (p < 0.01) improvement in VAS neck, arm, and low back scores between preoperative and postoperative. In addition, there was no significant improvement in the VAS leg and EQ-5D score in either of the groups. While no significant decrease was found in occipital neuralgia in group 1, it showed significant (p < 0.01) improvement in occipital neuralgia in group 2. Conclusions: Although the exact pathophysiology is unknown, cervical stabilization surgery and sacrification of the C2 nerve root in this surgery can, directly and indirectly, improve low back pain.